2014
DOI: 10.1093/gji/ggu240
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of azimuthal anisotropy in the NW Pacific from seismic ambient noise in seafloor records

Abstract: S U M M A R YWe analysed background surface waves in seismic ambient noise by cross-correlating continuous records of eight ocean bottom seismometers and nine differential pressure gauges deployed in the northwestern Pacific Ocean by the PLATE project. After estimating the clock delay and instrumental phase responses of differential pressure gauges by using cross-correlation functions, we measured average phase velocities in the area of the array for the fundamental-, first higher-and second higher-mode Raylei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 47 publications
4
46
0
Order By: Relevance
“…This Figure 1. The thin arrows are the azimuths at depths shallower than~20 km (blue) and deeper depths of~50-80 km (red) by previous studies: S08 (Shinohara et al, 2008) near area A and S14 (Shintaku et al, 2014) and T14 (Takeo et al, 2014) at southwest of the Shatsky Rise. The thick arrows represent fastest azimuths at a depth shallower than~20 km (blue) and deeper depths of~80-100 km (red) determined in this study.…”
Section: Broadband Dispersion Analysismentioning
confidence: 85%
“…This Figure 1. The thin arrows are the azimuths at depths shallower than~20 km (blue) and deeper depths of~50-80 km (red) by previous studies: S08 (Shinohara et al, 2008) near area A and S14 (Shintaku et al, 2014) and T14 (Takeo et al, 2014) at southwest of the Shatsky Rise. The thick arrows represent fastest azimuths at a depth shallower than~20 km (blue) and deeper depths of~80-100 km (red) determined in this study.…”
Section: Broadband Dispersion Analysismentioning
confidence: 85%
“…With a magnitude of 4.6%, the percent anisotropy beneath the JdF plate falls between values characteristic of slow‐ (3–4%) and fast‐spreading (6–7%) environments (Gaherty et al, ; Toomey et al, ; Song & Kim, ; Shintaku et al, ; Takeo et al, ). We speculate that the positive correlation between spreading rate and percent mantle anisotropy may be related to the partial off‐axis realignment of olivine LPO.…”
Section: Discussionmentioning
confidence: 99%
“…Seismic anisotropy measurements in the oceanic lithosphere away from spreading centers yield many observations of skew between the seismically fast propagation and paleo‐spreading directions (Morris et al, ; Raitt et al, ; Shearer & Orcutt, ; Shintaku et al, ; Takeo et al, ). While the magnitude of skew observed in these studies is typically >10° and exceeds the measurement error, its significance is not always discussed.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies based on the cross-correlation analysis of ocean bottom records have shown several features of the seismic wavefield recorded at the ocean bottom [e.g., Harmon et al, 2007;Yao et al, 2011;Harmon et al, 2012;Takeo et al, 2013Takeo et al, , 2014Tian and Ritzwoller, 2015]. In particular, it has been seen that the fundamental mode of Rayleigh waves is always present on the vertical component of ocean bottom noise records with periods between 3 and 10 s, whereas the first overtone appears only at short periods [Harmon et al, 2007;Yao et al, 2011].…”
Section: Introductionmentioning
confidence: 99%